2013
DOI: 10.1088/1009-0630/15/11/07
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Transverse Field Component on the Edge Effect in a Short-Gap Discharge

Abstract: In a general plane-parallel electrode system, the edge of the electrode will undermine the uniformity of the dielectric barrier discharge (DBD) because of the influence of the distorted electrical field. In this paper, the influence of the non-uniform electrical field on the edge effect of DBDs in a short-gap is investigated. We present some of the experimental results of DBDs produced by three kinds of convex-spherical electrodes. The results show that there is a dark area (the homogeneous discharge) in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…For the symmetric electrode geometry, on the one hand, the electric field at the electrode edge is stronger than that in the central region [17,22], which can generate more electron avalanches. On the other hand, it has been reported that there is a transverse electric field component at the electrode edge [12,23]. The spatial ions in the microdischarge channels at the electrode edge have a transverse movement under the effect of the transverse electric field, and drag the surface electrons through an electrostatic coupling force, which leads to the redistribution of the space charges.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the symmetric electrode geometry, on the one hand, the electric field at the electrode edge is stronger than that in the central region [17,22], which can generate more electron avalanches. On the other hand, it has been reported that there is a transverse electric field component at the electrode edge [12,23]. The spatial ions in the microdischarge channels at the electrode edge have a transverse movement under the effect of the transverse electric field, and drag the surface electrons through an electrostatic coupling force, which leads to the redistribution of the space charges.…”
Section: Resultsmentioning
confidence: 99%
“…But they did not provide an explanation for the role of the edge effect in pattern formation [13]. For the diffuse discharge at the electrode edge, less attention has been paid to the influence of the transverse electric field on discharge [12,23]. It has been reported in previous work that the transverse electric field at the electrode edge is responsible for the generation of diffuse discharge [12].…”
Section: Introductionmentioning
confidence: 97%